2016
DOI: 10.1117/12.2224027
|View full text |Cite
|
Sign up to set email alerts
|

Ice sheet features identification, glacier velocity estimation, and glacier zones classification using high-resolution optical and SAR data

Abstract: Ice sheet features, glacier velocity estimation and glacier zones or facies classification are important research activities highlighting the dynamics of ice sheets and glaciers in Polar Regions and in inland glaciers. The Cband inSAR data is of ERS 1/2 tandem pairs with one day interval for spring of 1996 and L-band PolinSAR data of ALOS-PALSAR-2 for spring of 2015 is used in glacier velocity estimation. Glacier classification is done using multi-temporal C-and L-band SAR data and also with single date full p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…The main approach of estimating the dry, wet and total snow cover is similar to the earlier studies (Nagler andRott, 2000, Thakur et al, 2016), however, the input data is C-band SAR from Sentinel-1A/1B satellites and algorithm uses Google earth Engine (GEE) codes to access, and analyses time series data, as recently demonstrated by (Snapir et al, 2019). The VH polarization is used with Sentienl-1 data, as it has shown higher sensitivity to dry and wet snow (Thakur et al, 2016) as compared to the VV polarization. The brief methodology flow chart is given in figure 3.…”
Section: Snow Cover Dynamics Using C-band Sar Datamentioning
confidence: 67%
See 3 more Smart Citations
“…The main approach of estimating the dry, wet and total snow cover is similar to the earlier studies (Nagler andRott, 2000, Thakur et al, 2016), however, the input data is C-band SAR from Sentinel-1A/1B satellites and algorithm uses Google earth Engine (GEE) codes to access, and analyses time series data, as recently demonstrated by (Snapir et al, 2019). The VH polarization is used with Sentienl-1 data, as it has shown higher sensitivity to dry and wet snow (Thakur et al, 2016) as compared to the VV polarization. The brief methodology flow chart is given in figure 3.…”
Section: Snow Cover Dynamics Using C-band Sar Datamentioning
confidence: 67%
“…These glacier are highly sensitive to short and long term variations in temperature and precipitation variations, as well as climate change, and in last 50 years, most of these glaciers have shown negative mass balance and snout retreat (Wagnon et al, 2007;Bhambari and Bolch 2011;Bolch et al, 2012, Dobhal et al, 2008Azam et al, 2012;Sharma et al, 2013;Pratap et al, 2016) as observed by remote sensing and traditional ground based glaciological measurements. The dynamics of these glacier can be effectively observed and mapped by RS based methods (Bhambari et al, 2012), which can quantity its area, length and elevation changes over time, as well as its surface velocity and glacier facies (Joughin, 2010;Berthier et al, 2005;Kumar et al, 2011;Bhardwaj et al, 2015;Thakur et al, 2016Thakur et al, , 2017a. The vast amount of free and multi-temporal optical and SAR data from various space agencies have opened new applications in the field of glacier dynamics monitoring.…”
Section: Glacier Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…All datasets were ortho-rectified with Aster GDEM (30m) in polar stereo graphic projections systems taken from Landsat 8 datasets. In first part of this work an image album has been made highlighting some of the major ice sheet features and glacier landforms present at Antarctica using ISRO's to identify additional ice sheet and glacier features which were not detected by optical data (Thakur et al, 2016). The CARTOSAT-2 high resolution images were used to identify and map some of the unique ice sheet and glacier features such as crevasses, sastrugi, nunatak, ice ridges, wind scoops, rim lines, moraines, blue ice area (BIA) and deposited snow (Fig.…”
Section: High-resolution Satellite Data Applicationsmentioning
confidence: 99%